Performance analysis of adaptive modulation and coding combined with transmit diversity in next generation mobile communication systems - Hwang, I; Jang, TW; Kang, MG; No, S; Son, J; Hong, DS; Kang, CE (ELSEVIER SCIENCE BV, 2004)
In this paper, we combine Adaptive Modulation and Coding (AMC) with Transmit Diversity (TD) to improve the performance of AMC in CDMA systems. An improved SNR increases a probability of selecting Modulation and Coding Scheme (MCS) level that supports higher data transfer rate. Therefore, higher average throughput can be achieved. As an open-loop TD, Space-Time block coding based Transmit antenna Diversity (STTD) is applied to AMC. For a closed-loop TD, Selection Transmit Diversity (STD) is combined with AMC. The results show that higher throughput is achieved by AMC-TD schemes. Compared to the conventional AMC, AMC-STTD scheme shows about 250 kbps increase in throughput. In addition, AMC-STD with two transmit antennas achieves about 420 kbps throughput improvement over the conventional AMC at 9 dB SNR in flat Rayleigh fading channel. (C) 2003 Published by Elsevier B.V.
Keywords: FADING CHANNELS